CFTR Regulates Early Pathogenesis of Chronic Obstructive Lung Disease in βENaC-Overexpressing Mice - Johannesson, Bjarki; Hirtz, Stephanie; Schatterny, Jolanthe; Schultz, Carsten; Mall, Marcus A. (PLOS ONE, 2012)
Background Factors determining the onset and severity of chronic obstructive pulmonary disease remain poorly understood. Previous studies demonstrated that airway surface dehydration in βENaC-overexpressing (βENaC-Tg) mice on a mixed genetic background caused either neonatal mortality or chronic obstructive lung disease suggesting that the onset of lung disease was modulated by the genetic background. Methods To test this hypothesis, we backcrossed βENaC-Tg mice onto two inbred strains (C57BL/6 and BALB/c) and studied effects of the genetic background on neonatal mortality, airway ion transport and airway morphology. Further, we crossed βENaC-Tg mice with CFTR-deficient mice to validate the role of CFTR in early lung disease. Results We demonstrate that the C57BL/6 background conferred increased CFTR-mediated Cl− secretion, which was associated with decreased mucus plugging and mortality in neonatal βENaC-Tg C57BL/6 compared to βENaC-Tg BALB/c mice. Conversely, genetic deletion of CFTR increased early mucus obstruction and mortality in βENaC-Tg mice. Conclusions We conclude that a decrease or absence of CFTR function in airway epithelia aggravates the severity of early airway mucus obstruction and related mortality in βENaC-Tg mice. These results suggest that genetic or environmental factors that reduce CFTR activity may contribute to the onset and severity of chronic obstructive pulmonary disease and that CFTR may serve as a novel therapeutic target.